Evaluation of training system and process in selected computer training institutes: a survey report - Jain, Ravindra; Agrawal, Richa R. (2007)
In the bottom line business world of today, the concerned professionals should place a very high priority on `Evaluation of Training', but in most cases, it is the least adequately carried out part of the training system/process which, therefore, needs the attention of all concerned intellectuals. The present study is an attempt to evaluate the sub-systems and practices pertaining to `Pre-training', `Post-training', `Learning-evaluation' and "trainees" feeling of satisfaction with the various facets of training". Such an evaluation is done with reference to select private sector and public sector computer training institutes. Trainees' feeling of satisfaction was found highly positive with a few exceptions. The sub-system of `learning evaluation' as also, by and large, found effective. However, a number of shortcomings were emerged in the design of the `evaluation system' itself as well as in the sub-systems of pre-training and post-training. In-depth and empirically tested analysis in this context is being presented in this paper. - Reproduced.
Keywords: Training